De Gênes à Gênes (1960-2001) : la constitution d’un répertoire transnational de l’émeute au prisme de sa visibilité - Julien Allavena (Laboratoire Italien)
This contribution takes the clashes between police forces and demonstrators that took place during the 2001 Genoa counter-summit as its starting point, in order to propose a genealogy of contemporary political riots embodied in the now regular formation of black block processions. To do this, it examines in parallel images of the riots in question and historical sequences linked to the history of the autonomous Italian movement, and then the transnational one. After discussing the issues involved in both iconographic and socio-historical research, this contribution sets out to reconstruct everything that ‘regulates’ this type of riot, starting with the short timeframe in which the events of Genoa 2001 took place, and then with the long timeframe of the history of autonomous movements, during which a set of practices gradually took root and were disseminated internationally in the form of a repertoire of riot action. The final section looks at how these circumstances shaped riotous political violence, demilitarising it in proportion to its visual stylisation.